2023
DOI: 10.1182/blood.2022016056
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel predisposing coding and noncoding variants in familial Hodgkin lymphoma

Abstract: Familial aggregation of Hodgkin lymphoma (HL) has been demonstrated in large population studies, pointing to genetic predisposition to this hematological malignancy. To understand the genetic variants associated with the development of HL, we performed whole genome sequencing on 234 individuals with and without HL from 36 pedigrees that had 2 or more first-degree relatives with HL. Our pedigree selection criteria also required at least one affected individual younger than 21 years of age, with the median age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…6 Recently, whole-genome sequencing of families with at least two first-degree relatives with HL demonstrated recurrent predisposing variants in several loci; these require validation but provide further evidence of germline predisposition in a subset of patients. 7 BIOLOGY HL is characterized by two main types, the more commonly diagnosed classic HL (cHL) and the rare nodular lymphocyte predominant HL, not the purview of this review. Among cHL, the most common subtype, nodular sclerosis, predominantly affects AYAs.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…6 Recently, whole-genome sequencing of families with at least two first-degree relatives with HL demonstrated recurrent predisposing variants in several loci; these require validation but provide further evidence of germline predisposition in a subset of patients. 7 BIOLOGY HL is characterized by two main types, the more commonly diagnosed classic HL (cHL) and the rare nodular lymphocyte predominant HL, not the purview of this review. Among cHL, the most common subtype, nodular sclerosis, predominantly affects AYAs.…”
Section: Epidemiologymentioning
confidence: 99%
“…6 Recently, whole-genome sequencing of families with at least two first-degree relatives with HL demonstrated recurrent predisposing variants in several loci; these require validation but provide further evidence of germline predisposition in a subset of patients. 7…”
Section: Epidemiologymentioning
confidence: 99%
“…Ongoing imaging mass cytometry on specimens from AHOD0031 and AHOD1331 will allow for high‐throughput evaluation of multiple proteins on both the HRS cell and the TME, and will lead to comprehensive characterization of the tumor cells and their interactions with stromal and immune components. Understanding genetic heritability of cancer and immune deficiency and corresponding predisposing loci could add to risk‐based therapy, which may have more relevance in younger pediatric patients 69 …”
Section: Recent Findingsmentioning
confidence: 99%
“…Understanding genetic heritability of cancer and immune deficiency and corresponding predisposing loci could add to risk-based therapy, which may have more relevance in younger pediatric patients. 69 Automated methods and application of artificial intelligence (AI) methods provide more reliable PET quantification for clinical and research applications with faster throughput for PET quantitation, such as MTV and total lesion glycolysis (TLG). 70 An ongoing analysis of FDG-PET quantitation using AI algorithms is being evaluated for its utility in risk stratification in AHOD1331, integrating clinical, radiolog-ical, and molecular biomarkers in a personalized dynamic risk model for predicting HL outcomes.…”
Section: Evaluation Of New Biomarkersmentioning
confidence: 99%
“…Both twin and case‐control studies have shown that the etiopathogenesis of HL has a significant genetic component 7 , 8 . While typically sporadic, familial clustering is found in approximately 4.5% of HL, allowing for Next Generation Sequencing‐based investigations for potential drivers of disease 9–15 . Functional effects of fHL‐associated variants (by expression in isogenic cell lines) have however been demonstrated by only 2 such studies: in the KLHDC8B gene (a promoter‐disrupting chromosomal translocation in 1 family and a recurrent 5’UTR variant in 3 others) 9 and the POT1 gene (2 different missense variants, in 2 families) 13 .…”
Section: Figurementioning
confidence: 99%